2008
DOI: 10.1523/jneurosci.5542-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

CLEC-38, A Transmembrane Protein with C-Type Lectin-Like Domains, Negatively Regulates UNC-40-Mediated Axon Outgrowth and Promotes Presynaptic Development inCaenorhabditis elegans

Abstract: In the developing nervous system, axons respond to various guidance cues to find their targets. The effects guidance cues have on an axon may change as an axon undergoes morphological changes, such as branching, turning, and synapse formation. The means by which these changes are regulated are not well understood. In Caenorhabditis elegans, the UNC-40/DCC (deleted in colorectal cancer) receptor mediates responses to the UNC-6/netrin guidance cue. Here, we show that CLEC-38, a protein with predicted transmembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…For example, in contrast to the unc-40(ur304) phenotypes, the expression of a constitutively activated UNC-40 protein, MYRTUNC-40, causes enlarged and deformed cell bodies and additional axons and branches, as well as misguided axons (Gitai et al 2003). Previously, we showed that loss of clec-38 enhances UNC-40 activity and that, in clec-38 loss-offunction mutants that express the unc-40Tgfp transgene, the HSN develops severe morphological defects (see Figure 7 in Kulkarni et al 2008). Moreover, we observed that UNC-40 at the early L2 stage is ventrally asymmetrically localized in these mutants (Figure 3).…”
Section: Resultsmentioning
confidence: 97%
“…For example, in contrast to the unc-40(ur304) phenotypes, the expression of a constitutively activated UNC-40 protein, MYRTUNC-40, causes enlarged and deformed cell bodies and additional axons and branches, as well as misguided axons (Gitai et al 2003). Previously, we showed that loss of clec-38 enhances UNC-40 activity and that, in clec-38 loss-offunction mutants that express the unc-40Tgfp transgene, the HSN develops severe morphological defects (see Figure 7 in Kulkarni et al 2008). Moreover, we observed that UNC-40 at the early L2 stage is ventrally asymmetrically localized in these mutants (Figure 3).…”
Section: Resultsmentioning
confidence: 97%
“…To our knowledge, chodl is the first C-type lectin to be implicated in axon pathfinding in vertebrates. In C. elegans another C-type lectin, CLEC-38, has been shown to be involved in dorsal axon guidance (Kulkarni et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Also, pathway analysis of genes illustrates how brain morphology and function may be influenced by processes including neuronal growth, migration, communication, and pruning. In this regard, axonal guidance signaling establishes normal connectivity between developing neurons and helps orient and promote axonal outgrowth (52,53). AKT2, PIK3CA , PIK3CB, and GNB3 were the relevant genes expressed in this signaling pathway.…”
Section: Discussionmentioning
confidence: 99%